Pengaruh Model Pembelajaran Numbered Head Together (NHT) Berbasis Realistik Terhadap Hasil Belajar Siswa. - Adela Istanto (IKIP PGRI Bojonegoro, 2014)
Strategy for Enhancing the Quality of Private Schools (Case StudyinSMP X Kab. Semarang). SMP X is one of the private formal educational institutions are faced with the problem how to improve its quality. Research which is conducted in the junior X aims to identify opportunities, threats, strengths and weaknesses junior X to the right strategic planning to increase quality. This research used qualitative methods. Data obtained from the parties who know the conditions and circumstances of junior X. The results showed there were opportunities, threats, strengths and weaknesses derived from SMP X. Those factors are dominant factors to improve the quality of junior X, because of deal with eight standardize education. Identification result of situations and conditions, itâ€™s formulated several strategies that can be used to improve the quality of SMP X. Some strategies are more focused on quality improvement through learning, fulfillment of infrastructures, quality improvementÂ of educators cooperation programs with other partnersip.Â Keywords: Opportunities, Threats, Strengths, Weaknesses, Strategy, Quality.